Relative telomere length and prostate cancer mortality. Issue 4 (November 2018) - Renner, Wilfried; Krenn-Pilko, Sabine; Gruber, Hans-Jürgen; Herrmann, Markus; Langsenlehner, Tanja
Abstract Purpose Telomeres are essential for the maintenance of chromosomal integrity and telomere length has been associated with cancer risk and development. Aim of the present study was to analyze the prognostic value of leukocyte relative telomere (RTL) length in long-term prostate cancer (PCa) mortality. Methods Blood samples of PCa patients were obtained before initiation of radiotherapy. RTL of peripheral blood leukocytes was determined by a quantitative polymerase chain reaction method in 533 patients with PCa. Main outcome was overall mortality. Results During a median follow-up time of 149 months, 188 (35.3%) patients died. In a univariate Cox regression analysis, RTL quartiles (longer RTL) were significantly associated with higher overall mortality (hazard ration (HR) = 1.20; 95% confidence interval (CI): 1.05–1.36;p = 0.006). In a multivariate Cox regression model including age at diagnosis, androgen deprivation therapy, and risk group (based on PSA level, GS, and T stage), RTL quartiles remained a significant predictor of higher overall mortality (HR = 1.22; 95% CI: 1.07–1.39;p = 0.003). Conclusions Longer leukocyte RTL predicts higher overall mortality in patients with PCa.